(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2022)
Objectives: Asians represent the fastest growing ethnic group in the United States. Despite significant diversity within the group, many transplant studies treat Asians as a homogeneous entity. We compared patient and graft survival among major Asian eth- nicities to determine whether any subgroup has superior out- comes. Methods: We conducted a retrospective analysis of kidney trans- plants on Asian and White patients between 2001 and 2012. Co- variates included gender, age, comorbidities, and donor category. Primary outcomes included one-year patient and graft survival. Secondary outcomes included delayed graft function (DGF) and rejection as cause of graft loss and death. Results: Ninety-one Asian patients were identified. Due to the large proportion of Chinese patients (n=37), we grouped other Asians into one entity (n=54) for statistical comparison among Chinese, other Asians, and Whites (n=346). Chinese subjects had significantly lower body mass index (BMI) (p=0.001) and had the lowest proportion of living donors (p>0.001). Patient survival was highest in our Chinese cohort (p>0.001) Discussion: Our study confirms outcome differences among Asian subgroups in kidney transplantation. Chinese demonstrate better patient survival at one year than Whites and non-Chinese Asians despite fewer live donors. Lower BMI scores may partly explain this. Larger, long-term studies are needed to elucidate outcome disparities among Asian subgroups